A Primer on Efficiency Measurement for Utilities and Transport Regulators - Coelli, Tim; Estache, Antonio; Perelman, Sergio; Trujillo, Lourdes (Washington, DC: World Bank, 2013)
This book is intended to help regulators learn about the tools needed to measure efficiency. It is based on lecture notes from courses the World Bank Institute offers in English, French and Spanish throughout the developing world and has benefited from feedback received during those courses. It provides an overview of the various dimensions of efficiency that regulators should be concerned with. It also summarizes the main quantification techniques available to facilitate decisions in the most common regulatory processes. The issues covered should be of particular interest to those policymakers and regulators interested in measuring relative efficiency and in implementing any incentive-based regulatory mechanism that requires the measurement of efficiency, such as price caps, revenue caps, or yardstick competition. The book focuses on methodology selection, data collection, and related issues. It provides readers with all the conceptual tools they need to make real-life decisions. It is also supported by a web site from which readers can download software they can use to implement the techniques described.